Multilevel Nonvolatile Memory by CMOS-Compatible and Transfer-free Amorphous Boron Nitride Film - Sattari-Esfahlan, Seyed Mehdi; Hyun, Sang Hwa; Moon, Ji Yun; Heo, Keun; Lee, Jae Hyun (ACS Applied Electronic Materials, 2024)
Exploiting the multistate characteristic, we have engineered a single memristor based on amorphous boron nitride (a-BN) capable of rivaling the logic capacity of multiple field-effect transistors (FETs). The quintessence of our work is the realization of quinary resistive switching with five distinct resistive states enabled by a wafer-scale, chemical vapor deposition (CVD) grown a-BN thin film. This feat is achieved directly on the substrate, eschewing the need for transfer processes and leveraging low-temperature synthesis. The device exhibits an exceptional On/Off ratio of ∼108, sustained over a significant cycling lifespan. We uncover the intricate interplay between the a-BN channel thickness and the quantized resistive states, revealing a precision-controlled resistive landscape. This capability addresses the production and transfer bottlenecks associated with two-dimensional materials, setting the stage for our a-BN-based memory device to advance the frontiers of ultrahigh-density data storage and computing systems.
Keywords: Amorphous boron nitride; Chemical vapour deposition; CMOS Compatible; Intermediate resistive switching state; Multilevel memory; Multilevels; Non-volatile memory; Resistive state; Resistive switching; Resistive switching memory; amorphous boron nitride; chemical vapor deposition; CMOS-compatible; intermediate resistive switching states; multilevel memory; resistive switching memory